REFORMULASI PERENCANAAN PEMBANGUNAN NASIONAL MODEL GARIS-GARIS BESAR HALUAN NEGARA - Ade Kosasih (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2019)
The inability of the national long-term development plan (RPJPN) to consolidate different programs between one President and the next President, results in unsustainable development plans. So there is a desire to revitalize the outlines of the state's direction (GBHN) as a guide to national development that was once able to integrate national development planning in the past. Therefore, it is necessary to reform the GBHN, because the concept of GBHN in the past is not necessarily relevant to the current state administration system, especially the implications of the GBHN on the authority of the MPR. The future GBHN systematics will be followed up with the RPJM and the regional mid-term development plan (RPJMD) in lieu of the five-year development plan. To strengthen the legality of GBHN as a development planning document, the MPR Decree on GBHN must be interpreted as a fundamental norm, so that if the President deviates from the GBHN, then the President can be impeached. This means that the position and function of the MPR and the Constitutional Court (MK) need to be reconstructed, that is, the MPR is given the authority to submit impeachments and execute MK Decisions related to impeachment of the President in violation of the GBHN, while the Constitutional Court has the authority to examine and adjudicate requests for impeachment. Thus, it is believed that development planning can run in an integrated and sustainable manner.